MONTREAL EXCLUSIVITY VERSUS EU LAW - Đurđev, Dušanka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Current air law is a showcase of multilevel regulation. The rights and obligations of airlines and their passengers are governed both by the Montreal Convention and by EU Regulation 261/2004. The EU placed itself in a difficult position by adopting Regulation 261/2004 shortly after it had signed the Montreal Convention. Both instruments provide for different standards for liability. The issue is whether or not the rules in the Convention is exclusive.